The Comparison of Er α Expression Between Endometriosis with No Endometriosis - Syafardi, D. Irsat; Siregar, Hendry Salim; Kaban, Yostoto B; Ardiansyah, Edy (Sumatera Medical Journal, 2019)
Estrogen receptors (ER) play an important role in mediating action. The ER α has a higher affinity for estrogen and the dominant form of the normal endometrium. A cross-sectional study from an ectopic tissue of endo-metriosis and normal was examined for immunohistochemistry. This research was conducted from November 2015 until the sample complete. The analysis was performed using Fisher Exact test, p <0.05 was considered to any difference of estrogen alpha receptor expression between endometriosis patients with no endometriosis. REα is more dominant in normal endometrium, whereas in the case of endometriosis in the presence of many negative expression of REα then the assumption that REβ is a receptor that many encountered. There is a dif-ference in the expression of REα between endometriosis with no endometriosis.